Computed Tomography-Guided Percutaneous Drainage of Pneumomediastinum in a Newborn: A Case Report - (:unkn) unknown (My University, 2021)
BACKGROUND: Neonatal pneumomediastinum is seen in 2.5 per 1000 live births and mostly managed conservatively. An intervention is essential in cases with tension pneumomediastinum. Ultrasonography-guided (USG-guided) relief of pneumomediastinum has been reported in newborns. There are no reported cases of computed tomography-guided (CT-guided) drainage of pneumomediastinum in neonates. CASE REPORT: A newborn girl born at 34 week of gestation was intubated due to respiratory distress and received intratracheal surfactant treatment. Pneumomediastinum was detected at the chest X-ray on the 6th postnatal hour. On the second postnatal day, the patient's oxygen needs increased, tachypnea and subcostal retractions recurred, so it was decided to intervene. USG-guided drainage of the pneumomediastinum was attempted twice but was unsuccessful. Percutaneous drainage with CT guidance was performed successfully. CONCLUSION: This report aims to emphasize that CT-guided intervention of pneumomediastinum can be an effective alternative in a newborn if USG-guided intervention fails.
Keywords: ultrasonography; newborn; Case report; computed-tomography; pneumomediastinum; respiratory distress